Search for direct pair production of scalar top quarks in the single- and dilepton channels in proton-proton collisions at root s=8 TeV - (:unkn) unknown (SPRINGER, 2016)
are reported from a search for the top squark (t) over tilde (1) , the lighter of the two supersymmetric partners of the top quark. The data sample corresponds to 19.7 fb(-1) of proton-proton collisions at root sv - 8 TeV collected with the CMS detector at the LHC. The search targets (t) over tilde (1)-> b (x(1)) over tilde (+/-) and (t) over tilde (1)-> t((*)) (x) over tilde (0) decay modes, where (x(1)) over tilde (+/-) and (x) over tilde (0) are the lightest chargino and neutralino, respectively. The reconstructed final state consists of jets, b jets, missing transverse energy, and either one or two leptons. Leading backgrounds are determined from data. No significant excess in data is observed above the expectation from standard model processes. The results exclude a region of the two-dimensional plane of possible (t) over tilde (1) and (x(1)) over tilde (0) masses. The highest excluded (t) over tilde (1) and (x(1)) over tilde (0) masses are about 700 GeV and 250 GeV, respectively.
Keywords: Hadron-Hadron scattering (experiments); Supersymmetry; top squark; P(P)OVER-BAR COLLISIONS; PP COLLISIONS; DARK-MATTER; SQUARK; EVENTS; BOSON